Determinants of the Use of Traditional Contraceptive Methods in Indonesia (2017 IDHS Data Analysis) - Henny Fatmawati; Evi Martha (Jurnal Ilmu Kesehatan Masyarakat, 2022)
The 2017 IDHS shows that modern family planning tools/methods tend to decrease while traditional family planning methods increase. This study aimed to determine the factors associated with using conventional contraceptives in Indonesia. This study uses secondary data from the 2017 IDHS. The sample size is 11,542 women of childbearing age 15-49 years. The dependent variable in this study was the use of traditional contraceptives. In contrast, the independent variables consisted of age, education level, mother's occupation, economic status, area of residence, number of children, desire to have children, the decision to use contraception, knowledge of family planning tools/methods, knowledge of fertile periods, visits by field officers, sources of information from the mass media, and ownership of health insurance. The analysis results show that women of childbearing age who are <20 years old or >35 years old, have a higher education level, and live in urban areas tend to use traditional contraceptive methods. Furthermore, women of childbearing age with good knowledge about family planning methods and their fertile period also tend to use traditional contraceptive methods. In addition, the husband's decision to use contraception and not to accept visits by field workers also influences women of childbearing age to use traditional contraceptive methods. The sources of information from the mass media and the use of conventional contraceptives were not different. BKKBN, through Family Planning Field Officers (PLKB), needs to socialize the family planning program so that it can motivate people to switch to modern contraceptive methods, especially long-term contraceptive methods.